Dating can be deadly - Flower, Amanda (Flower, Amanda, Amish matchmaker mystery, 2023)
"It's August in Holmes County, and that means it's time for the Holmes County Fair. It's the county's biggest annual event, drawing tourists and locals alike to see livestock, eat too much fried food, and watch the rodeo and speed racing contests. This year, Millie has entered the quilting competition -- while her very not Amish best friend, Lois Henry, is distracted by her new dating app and her search for husband number five. In a place where quilting is a way of life, the competition is fierce -- especially this year, when an anonymous donor doubles the winning cash prize. Amish and English women are up against each other, and some will do anything to win -- even murder ... When someone attacks the quilt barn by slashing the quilt display, it's unsettling enough. But when a quilting judge is found murdered, Millie knows it's time to for Lois to get off her app and help her hunt for a killer instead -- before the competition is wiped out for good..."--